Riegeriana, a new genus for Physopelta apicalis, and checklist of the genus Iphita (Hemiptera: Heteroptera: Largidae) with description of one new species - Stehlík, Jaroslav L.; Kment, Petr (Zootaxa, 2014)
Riegeriana gen. nov. is described to accommodate Physopelta apicalis Walker, 1873. A lectotype of Ph. apicalis is de-signated. Iphita fasciata Stehlík & Jindra, 2008, syn. nov., is recognized as a new junior subjective synonym of Riegeriana apicalis. In addition, Iphita lata sp. nov. is described from southern India and a check-list of the species of the genus Iphita Stål, 1873 is provided. The etymology of Iphita nigris Ahmad & Abbas, 1992 and the lectotype designation of Dindymellus coimbatorensis Distant, 1919 are discussed. The following new or confirmed country records are provided: Iphita coimbatorensis (Distant, 1919) from India (Karnataka, Orissa); I. dubia (Breddin, 1901) from Indonesia (Papua); I. limbata Stål, 1870 from Cambodia, China (Hainan), India (Arunachal Pradesh), Indonesia (Sumatra, Kalimantan), Malaysia (Pahang: Tioman Island), and Vietnam; I. lycoides (Walker, 1873) from the Philippines (Panay Island).